KEGIATAN MOBIL PINTAR DALAM MENDUKUNG PROGRAM MERDEKA LITERASI DI DESA TANJUNG BURUNG - Sitompul, Lastiar Roselyna; Patricia Tantu, Year Rezeki; Tangkin, Wiyun Philipus; Silalahi, Destya Waty (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Literacy skills in students are the basis for learning in various fields. With good literacy skills, students will be able to learn independently, understand instructions and tasks better, and access the information necessary to develop knowledge and skills. But the literacy skills of children in Tanjung Burung village are very lacking. Many kindergarten-age children do not know letters, and low-grade elementary students cannot read. Social and economic factors affect the quality of education in Tanjung Burung with the village category being very underdeveloped. Such as village conditions, PKM activities are carried out in Tanjung Burung village aimed at supporting the independent literacy program by developing children's literacy skills through learning materials tailored to children's characteristics, through the assistance of tutors. This method of activity includes the stages of preparation, implementation, and evaluation activities. The result obtained from this activity is that kindergarten-age children have been able to recognize the letters A-Z and develop motor skills (through movement and song). For the age of low-grade elementary school children have been able to group (inanimate objects, living objects, family members, means of transportation), introduce themselves with simple sentences, and recognize numbers in the form of children's stories, while for the age of the high-grade elementary school, children have been able to compose sentences, make short stories, explain unit values, tens, and hundreds.